Analysis of the Effect of ZnO, FeO, MnO, and MgO Dopants on the Optical Properties of P2O5-CaO Glass System and Comparison With P2O5-Eggshell Glass System - Haifany; Eka Laela Nun Karina; Selsa Sururiyah Sya’baniah; Zahra Sajidah Hariyawan; Haryanto; Agus Setyo Budi; Anggara Budi Susila; Hadi Nasbey (Spektra: Jurnal Fisika dan Aplikasinya, 2025)
This study investigates the effect of ZnO, FeO, MnO, and MgO dopants on the optical properties of phosphate-based glass within the P₂O₅–CaO system and compares the results with glasses using eggshell-derived CaO as an alternative calcium source. The glass samples were synthesized using the melt quenching method, followed by characterization using Energy Dispersive X-ray (EDX) and UV-Visible spectroscopy. EDX analysis confirmed that phosphorus and oxygen were the dominant elements in all samples, with successful incorporation of each dopant as a network modifier. UV-Vis analysis revealed that the optical properties of the glass were significantly affected by both dopant type and concentration. The addition of ZnO decreases absorbance and widens the band gap up to 10 mol%, indicating improved structural regularity of the glass network. MnO exhibits a non-linear trend, with the highest absorbance observed at 5 mol% and decreasing at higher concentrations. The band gap varies from 3.37 eV to 3.59 eV, suggesting a transition from a disordered to a more stable and compact glass structure. In contrast, FeO and MgO doping reduced the band gap energy due to increased formation of non-bridging oxygen and network disruption. Additionally, comparison with eggshell-derived CaO showed higher UV absorbance compared to glass made with pure CaO, especially in the wavelength range below 400 nm, indicating that the raw material source influences the optical performance of the glass. Overall, this research highlights the potential of tuning dopant concentration and utilizing sustainable raw materials to enhance the optical characteristics of phosphate glass for use in UV-blocking, optoelectronic, and sensor applications.